A conserved tryptophan in the acylated segment of RTX toxins controls their β2 integrin-independent cell penetration - Osickova, Adriana; Knoblochova, Sarka; Bumba, Ladislav; Man, Petr; Kalaninova, Zuzana; Lepesheva, Anna; Jurnecka, David; Cizkova, Monika; Biedermannova, Lada; Goldsmith, Jory A; Maynard, Jennifer A; McLellan, Jason S; et al. (The Journal of biological chemistry, 2023)
The acylated Repeats in ToXins (RTX) leukotoxins, the adenylate cyclase toxin (CyaA) or α-hemolysin (HlyA), bind β2 integrins of leukocytes but also penetrate cells lacking these receptors. We show that the indoles of conserved tryptophans in the acylated segments, W876 of CyaA and W579 of HlyA, are crucial for β2 integrin-independent membrane penetration. Substitutions of W876 by aliphatic or aromatic residues did not affect acylation, folding, or the activities of CyaA W876L/F/Y variants on cells expressing high amounts of the β2 integrin CR3. However, toxin activity of CyaA W876L/F/Y on cells lacking CR3 was strongly impaired. Similarly, a W579L substitution selectively reduced HlyA W579L cytotoxicity towards cells lacking β2 integrins. Intriguingly, the W876L/F/Y substitutions increased the thermal stability (Tm) of CyaA by 4 to 8 °C but locally enhanced the accessibility to deuteration of the hydrophobic segment and of the interface of the two acylated loops. W876Q substitution (showing no increase in Tm), or combination of W876F with a cavity-filling V822M substitution (this combination decreasing the Tm closer to that of CyaA), yielded a milder defect of toxin activity on erythrocytes lacking CR3. Furthermore, the activity of CyaA on erythrocytes was also selectively impaired when the interaction of the pyrrolidine of P848 with the indole of W876 was ablated. Hence, the bulky indoles of residues W876 of CyaA, or W579 of HlyA, rule the local positioning of the acylated loops and enable a membrane-penetrating conformation in the absence of RTX toxin docking onto the cell membrane by β2 integrins.
Keywords: buněčná membrána; Adenylate Cyclase Toxin; tryptofan; antigeny CD18; thermal stability; Erythrocytes; tryptophan residue; konzervovaná sekvence; Tryptophan; Bordetella pertussis; β(2) integrins; hydrogen/deuterium exchange; Conserved Sequence; acylated segment; α-hemolysin; erytrocyty; RTX toxin; cytotoxicity; CD18 Antigens; Cell Membrane; adenylátcyklasový toxin; adenylate cyclase toxin